Stack shut-down strategy optimisation of proton exchange membrane fuel cell with the segment stack technology. (1st January 2020) - Lin, Rui; Liu, Dengcheng; Xia, Shixiang; Ma, Tiancai; Dutruel, Benjamin
Abstract: In the previous researches, researchers mainly focus on the single cell which is far away from the practical application. In this paper, shut-down process is studied in a 5-cell stack with segment technology. In the unprotected group, the hydrogen/air boundary is observed, and the output voltage performance degrades greatly after 300 start-stop cycles. A 2-phase auxiliary load strategy is proposed to avoid the hydrogen/air boundary. The lifetime is extended. But a serious local starvation is observed during the shut-down process. And corrosion happened in the inlet region. To avoid the starvation, the second strategy is designed, which combines 2-phase auxiliary and air purge (2-phase load& air purge strategy). With the new strategy, the degradation of the stack after 1500 cycles is acceptable, and the carbon corrosion in the inlet is effectively reduced. It could conclude that the hydrogen/air boundary is the main cause of the degradation of fuel cell during an unprotected shut-down process. And a strategy only with auxiliary load may suffer from the local starvation. The purge process can avoid the vacuum effect in the fuel cell caused by the auxiliary load. Therefore, adding an air purge during the shut-down process is promising in vehicle fuel cell. Graphical abstract: Image 1 Highlights: Using stack segment cell technology to optimize shut-down strategy. H2/air boundary in different cell is observed. Local starvation caused by auxiliary load may damage the inlet part. 2-phase load& air purge strategy shortens H2/air boundary duration. 2-phase load& air purge strategy also avoids local starvation.